A comparative performances analysis of UHF RFID two crossed dipoles antenna based on FR4 substrate. Issue 9 (11th August 2018) - Ben Abdallah, E.; Egels, M.; Bergeret, E.; Benzaim, O.; Pannier, P.
Abstract: The design of an FR4‐based UHF RFID portable quasi‐isotropic reader antenna with a circular polarization is reported. This low‐cost small size antenna consists of two crossed dipoles with dimensions of 50 × 80 × 1.6 mm 3 . A 3‐dB axial ratio bandwidth of 10 MHz can be obtained and a quasi‐isotropic radiation pattern is achieved. The designed antenna performances are investigated for 6 prototypes using the same substrate and different boards. A performances comparison and analysis between the different realizations are presented in this article. Results demonstrate that inaccuracies in FR4 characteristics have effects on the antenna performances. Therefore, the key parameters of this type of antennas are identified.